2023
DOI: 10.1037/cdp0000605
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-racial identity and ethnic-racial socialization competency: How minoritized parents “walk the talk”.

Abstract: Objectives: Ethnic-racial identity (ERI) has important implications for individual psychosocial functioning as well as familial processes. For example, parents' ERI can shape children's developmental contexts through ethnic-racial socialization (ERS). Yet, existing research has tended to focus on the content or frequency of socialization messages themselves rather than on internal factors like socialization competence. Such competence, as reflected through confidence, skills, and stress, represents critical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The relation of these other factors to ERS could be explored in future research on monoracial AAPIs. Particular focus should be given to how parents' ethnic-racial identity and attitudes, shaped by the context, inform parents' ERS practices (Kiang et al, 2023). Relatedly, the role of parents' critical consciousness (Christophe et al, 2022) should be explored.…”
Section: Child and Parent Factorsmentioning
confidence: 99%
“…The relation of these other factors to ERS could be explored in future research on monoracial AAPIs. Particular focus should be given to how parents' ethnic-racial identity and attitudes, shaped by the context, inform parents' ERS practices (Kiang et al, 2023). Relatedly, the role of parents' critical consciousness (Christophe et al, 2022) should be explored.…”
Section: Child and Parent Factorsmentioning
confidence: 99%
“…Parents with higher levels of REI centrality may have more cultural knowledge to draw upon, and those who have a higher private regard for their own racial–ethnic group may be more cognizant of the threat of racism for their children. In a study on Asian American parents with adolescents, while RES practices were not measured, Kiang et al (2023) found that parents’ REI private regard and centrality were both associated with greater confidence and perceived skill in their RES ability (i.e., RES competency). Since higher RES competency has been linked to higher rates of cultural heritage maintenance and preparation for bias, and lower rates of minimizing race (Christophe et al, 2022), a similar pattern could be observed between parental REI and their RES engagement.…”
Section: Factors That Shape Parental Res Among Asian American Familiesmentioning
confidence: 99%